A STUDY ON ONLINE BANKING & FINANCIAL INCLUSION OF WOMEN STREET VENDORS IN PUNE - Khandagale, Aniket Sanjay; Shetiya, Mahavir Manikchand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the impact of online banking services on the empowerment of women, specifically focusing on street vendors in the Pune region. The study aims to assess how the adoption of online banking facilitates financial independence, security, and growth opportunities for these women. By examining various dimensions of empowerment, including economic stability, access to credit, and financial literacy, this paper provides insights into the transformative potential of digital financial services for marginalized women.